Strengthening disability studies through legal perspectives : the case of Malaysia - Md Tah, Ikmal Hisham; Mokhtar, Khairil Azmin (Universiti Teknologi MARA (Terengganu), 2016)
Disability studies has created keen interest of many scholars from various academic fields including medicine, sociology, and education. Studies of these areas on disability have become major threshold in understanding the needs of persons with disabilities (PWD), which is one of the minority groups that have significant role and importance in the community. What is the best approach in dealing with PWD affairs? There is debate on this issue because initially there are at least two choices or models to be followed namely the medical model and the social model. With the existence of the Convention on the Rights of Persons with Disabilities (CRPD), an international human rights treaty that specifically addressed the rights and needs of PWD, legal perspective has penetrated into forming a new understanding of disability studies. The concept of rights, for example, has become the cause of major discussions within the social model. The discussions on the legal aspect and rights of PWD have eventually formed an integral part of understanding the model. Thıs paper asserts that legal perspective has strengthened the disability studies generally. It also attracts potential scholars to have academic discourse on the studies at present and in future globally and locally. Malaysia as one of the Sate Members of the CRPD has enacted a domestic legislation known as Persons with Disabilities Act 2008 to fulfill its the obligations under the treaty. The doctrinal legal research adopted by this paper explores the relationship between disability studies and legal studies within the context of Malaysian legal framework. It is believed there is a strong link between the two studies which is waiting to be properly and fully utilised. The combined studies of both areas create a fertile academic environment which can give rise to academic discourses of multiple fields. Such interdisciplinary approach will add value to the research and make the outcome more practical in promoting and protecting the rights of PWD. There is a dire need to strengthen disability studies through legal perspectives because it would allow greater and meaningful participation from whole society to address the concern and grievances suffer by this important by the marginalized group.